Bayah Dome Geopark Information System Based On Website Using Prototype Method - Karyaningsih, Dentik; Fernando, Donny; Pramudita, Reza; Ramadhan, Fauzan Wahyu (Universitas Trilogi, 2023)
To realize a national Geopark and a World Geopark, it is necessary to socialize and disseminate information that can be accessed by the people of Lebak Regency in particular and the wider community in general to introduce all the geological heritage that has been determined by the Minister of Energy and Mineral Resources. Nowadays, digital information system technology has become an undeniable need, and has even become a source of information that can be accessed by all people in the world. The Bayah Dome Geopark management body in Lebak Regency does not yet have a website-based information system, so it is necessary to create a website-based Bayah Dome Geopark information system so that the Bayah Dome Geopark is known nationally and internationally.This research uses a Research and Development approach. Research procedures include: (a) analysis, (b) design, (c) implementation and (d) evaluation. Stage (a) analysis consists of two steps, namely literature study and field survey. The literature study examines concepts and theories relating to Geoparks and the Bayah Dome Geopark, while a field survey was carried out to collect data relating to the Bayah Dome Geopark. Stage (b) design is carried out by designing a website with UML (Unified Modeling Language) which is a program design based on the results obtained in the analysis stage which includes: use case diagrams, activity diagrams using the prototype system development method. In stage (c) implementation, the results of the design are outlined and implemented into a website.